2010
DOI: 10.1111/j.1751-1097.2009.00683.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Photoacoustic Monitoring of Photosensitizer Distribution in Burned Skin for Antibacterial Photodynamic Therapy

Abstract: For efficient antibacterial photodynamic therapy for wounds, information on the distribution of a photosensitizer in tissue is important, but conventional fluorescence measurement does not provide depth-resolved information. We previously proposed in vivo photoacoustic (PA) depth profiling of a photosensitizer, but the contrast of PA signals was not sufficiently high, mainly due to light absorption by blood in tissue. In this study, we performed dual-wavelength PA measurement; green light and red light were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…While TB, MB are hydrophilic with a negative log (P) value (19,20), CV, ET, NPe6, NMB, RB and PHP are amphiphilic with progressively higher positive log (P) values (20)(21)(22)(23)(24)(25)(26). The cell membrane of a mammalian cell is composed of doublelayered phospholipids, and hydrophilic molecules therefore cannot permeate the cell membrane, while amphiphilic and hydrophobic molecules can easily permeate the cell membrane and be promptly transported into the cell (27).…”
Section: Discussionmentioning
confidence: 99%
“…While TB, MB are hydrophilic with a negative log (P) value (19,20), CV, ET, NPe6, NMB, RB and PHP are amphiphilic with progressively higher positive log (P) values (20)(21)(22)(23)(24)(25)(26). The cell membrane of a mammalian cell is composed of doublelayered phospholipids, and hydrophilic molecules therefore cannot permeate the cell membrane, while amphiphilic and hydrophobic molecules can easily permeate the cell membrane and be promptly transported into the cell (27).…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that PDT using TB or MB could preserve host neutrophils (>80% viability) while killing substantial amounts of MRSA (5–6 logs of killing). While TB and MB are hydrophilic with a negative easured (P) value [133,134], crystal violet, erythrosine B, NPe6, new MB, rose bengal and PHP are amphiphilic with progressively higher positive log (P) values [129]. Both mammalian cell and bacteria membrane are composed of double layered phospholipids, but the bacterial cell membrane is encased in a cell wall [135].…”
Section: Finding a Selective Ps For Pdt Of Bacterial Arthritismentioning
confidence: 99%
“…Photosensitizer dosimetry was assessed by photoacoustic signals from the photosensitizer in tissue in a study aimed at combating antibiotic-resistant bacteria. In vivo photoacoustic signals were resolved from MB or Photofrin that was injected into burned skin of rats for profiling of the sensitizer up to 3 mm in depth (31). Other themes in photodynamic action were also represented.…”
Section: Photodynamic Actionmentioning
confidence: 99%